Oxidant and Antioxidant Parameters' Assessment Together with Homocysteine and Muscle Enzymes in Racehorses: Evaluation of Positive Effects of Exercise - Francesca Arfuso; Maria Rizzo; Claudia Giannetto; Elisabetta Giudice; Roberta Cirincione; Giovanni Cassata; Luca Cicero; Giuseppe Piccione (MDPI AG, 2022)
This study aimed to evaluate the changes in serum oxidant and antioxidant parameters together with the serum values of homocysteine (Hcy) and muscle enzymes including creatine kinase (CK), aspartate aminotransferase (AST) and lactate dehydrogenase (LDH) in regularly trained athletic horses during official races of 1200, 1600 and 2000 m. Thirty Thoroughbred horses were divided into three groups of 10 subjects each according to the race distance: Group 1, 1200 m race; Group 2, 1600 m race; Group 3, 2000 m race. Blood samples were collected from horses 1 week prior to the race (1WB), on the day of the race at rest (TREST), immediately after the race (TPOST), and after 30 (TPOST30) and 120 (TPOST120) minutes. Serum total proteins, reactive oxygen metabolites (dROMs), thiol antioxidant barrier (SHp), antioxidant barrier (Oxy-ads), Hcy, CK, AST and LDH values were assessed. A two-way repeated measures ANOVA did not show differences referable to the race distance (Group effect) on all investigated parameters (p > 0.05). An exercise effect on oxidative stress markers, Hcy and muscle enzymes herein investigated was found in all groups (p < 0.001). A Pearson's test showed dROMs positively correlated with SHp, Oxy-ads and Hcy after exercise (p < 0.05). This study suggests that, though well-trained racing horses are subjected to oxidative stress during a race, a proper antioxidant capacity may improve their ability to cope with exercise-induced oxidative stress.